Bio-conversion of photosynthetic bacteria from non-toxic wastewater to realize wastewater treatment and bioresource recovery: A review. (April 2019) - Lu, Haifeng; Zhang, Guangming; Zheng, Ziqiao; Meng, Fan; Du, Taisheng; He, Shichao
Graphical abstract: Highlights: PSB wastewater treatment and resource recovery technology was reviewed. PSBs classification, metabolism, and the market application were described. The feasibility, procedures, bioreactors of this technology were summarized. Feasibility and potential of PSB non-toxic wastewater treatment was evaluated. Issues that concern the industrialization at the plant scale were listed. Abstract: Generating or recycling water and resources from wastewater other than just treating wastewater is one of the most popular trends worldwide. Photosynthetic bacteria (PSB) wastewater treatment and resource recovery technology is one of the most potential methods. PSBs are non-toxic and contain lots of value-added products that can be utilized in the agricultural and food industries. They are effective to degrade pollutants and synthesize useful biomass, thus realizing wastewater treatment, bioresource production, and eliminating waste sludge. If all the nutrients in wastewaters could be bio-converted by PSB, then pollutant reductions and economic benefits would be achieved. This review paper firstly describes and summarizes this technology, including PSBs classification, metabolism, and the market application. The feasibility, technical procedures, bioreactors, pollutant removal, and bioresource production are also summarized, compared and evaluated. Issues that concern the advantages and industrialization of this technologies at the plant scale are also discussed.